Neural Threat Processing in Individuals with Small-Animal Phobia Is Shaped by Cluster C Personality Traits - Ascensión Fumero; Francisco Rivero; Rosario J. Marrero; Alessandro Grecucci; Teresa Olivares; Wenceslao Peñate (European Journal of Investigation in Health, Psychology and Education, 2026)
Small-animal phobia (SAP) is characterized by exaggerated fear responses to biologically relevant threat cues, yet the extent to which personality traits influences neural threat processing remains unclear. This study examined whether Cluster C personality traits (avoidant, dependent, and obsessive–compulsive) modulate neural responses to phobic stimuli in SAP. Functional magnetic resonance imaging (fMRI) data were collected from 39 individuals with SAP and non-phobic controls while viewing phobia-relevant and neutral stimuli. Whole-brain analyses were conducted to identify group differences in brain activation, and additional models assessed the influence of Cluster C personality traits on neural responses. Compared with controls, individuals with SAP showed greater activation in regions involved in threat processing and emotional salience, including the anterior cingulate cortex, parahippocampal gyrus, pallidum, fusiform gyrus, and thalamus. Higher avoidant traits were associated with increased activation in visual regions implicated in threat detection, whereas dependent and obsessive–compulsive traits were linked to greater recruitment of prefrontal areas involved in cognitive control and emotion regulation. These findings suggest that neural responses to phobic stimuli are influenced not only by the presence of SAP but also by personality-related vulnerability, highlighting the role of Cluster C traits in shaping perceptual and regulatory aspects of threat processing.